Work Environment, Compensation, and Supervision on Job Satisfaction and Teacher Performance at SMA Negeri 1 Kampar - Juprizon; Teddy Chandra; Dadi Komardi (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
This study aims to analyze the work environment, compensation, and supervision effect on job satisfaction and teacher performance at SMA Negeri 1 Kampar. This research is quantitative research by distributing questionnaires to respondents. The sample in this study were all teachers of SMA Negeri 1 Kampar totaling 63 people. The sample selection method in this study used the census, so the sample in this study amounted to 63 respondents. Data analysis using Structural Equation Modeling (SEM) using the SmartPLS 3 application. The results of this study indicate that the work environment has a positive and significant effect on job satisfaction, compensation has no significant effect on job satisfaction, supervision has a positive and significant effect on job satisfaction, and work environment has a positive and significant effect on teacher performance, compensation has no significant effect on teacher performance, supervision has no significant effect on teacher performance, and job satisfaction has a positive and significant effect on teacher performance.